Factor Affecting Safety Performance Construction Industry - Nawi, Mohd Nasrun Mohd; Ibrahim, Siti Halipah; Affandi, Rohaida; Rosli, Nor Azalina; Basri, Fazlin Mohamad (International Review of Management and Marketing, 2017)
Construction industry is undoubtedly plays a significant role in the development process of a country. However, statistics have shown that construction industry is one of the most dangerous fields due to the fatality rates. The main cause of accident is due to poor safety performance of the workers from a combination of contributing causes. In order to improve the safety performance, the root causes of construction accidents and factors affecting them are needed to be investigated. The aim of this research is to evaluate in general the current factors affecting safety performance in construction industry in order to minimize the frequency of accident occurrence. Data were obtained through literature review and distribution of questionnaires, which were analyzed by using Likert scaling method. The results indicate the most critical types of accident are fall. While the most significant factor that affects safety performance is awareness; (1) not well educated, (2) differences in age, with different level of awareness, and (3) no safety briefing/ toolbox meeting. Thus, the suggestion to minimize accidents caused by poor safety performance is also by increasing the level of awareness through commitments from highest level of company by ensuring that the employees make proper use of all necessary practicable measures. Regular toolbox meeting before work commences should be practicable as it is one of the ways for information to be conveyed to the workers related to hazards or any other difficulties they faced. Apart from that, by increasing the number of safety signage to ensure that the staffs and visitors are well aware of the dangers and hazards ahead in certain situations or environments. Keywords: Construction Industry, Accidents Prevention, Risk Control JEL Classifications: L74, G31